Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

Mobilisations féminines au Cameroun français dans les années 1940-1950: l’ordre du genre et l’ordre colonial fissurés - Ndengue, Rose (Le Mouvement Social, 2016)
Durant la décennie qui suit la Seconde Guerre mondiale, le Cameroun sous tutelle française, comme tous les territoires de l’Empire colonial français, connaît une effervescence sociale et politique. Celle-ci se traduit par des mobilisations de Camerounaises et une montée en puissance de revendications nationalistes, face à l’insuffisance des réformes politiques et sociales mises en place. Cet article examine la manière dont, en s’inscrivant dans un paysage politique majoritairement masculin, des Camerounaises essayent de faire entendre leur voix en s’organisant pour défendre leurs intérêts. L’analyse des ressorts sur lesquels reposent les mobilisations féminines au Cameroun, met en évidence la dualité qui régit la présence des femmes sur la scène publique dans le contexte colonial. Dans une certaine mesure, leur démarche se situe dans un prolongement de l’imaginaire social dominant, mettant en avant des valeurs domestiques pour justifier une intervention des femmes sur la scène politique. Mais les mobilisations féminines visent également la défense d’un agenda propre aux femmes, ainsi que l’émergence d’un nouvel imaginaire social régi par l’égalité des sexes.
Keywords: 1900-1999; 1940-1949; 1950-1959; afrique; afro-féminisme; approches et analyses; cameroun; cours; discipline; discours dominant; féminisme africain; histoire; histoire et politique; militance; pol4022; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques